Continuous signals and systems with MATLAB® - Elali, Taan S. (Electrical engineering textbook series, 2021)
"The book offers broad, detailed, and focused comprehensive coverage of continuous linear systems, based on basic mathematical principles. It presents many solved problems from various engineering disciplines using analytical tools as well as MATLAB. This book is intended primarily for undergraduate junior and senior electrical, mechanical, aeronautical, and aerospace engineering students. Practicing engineers will also find this book useful"- Resumé vydavatel